Computed Tomography Scan Brain Tumor on suspicion General Hospital Haji Adam Malik: Computed Tomography Scan Brain Tumor on suspicion General Hospital Haji Adam Malik - Sri Nanda Sihotang; Nelida Erlince Pasaribu; Juliana Gustima Sinaga (Institute Of Computer Science (IOCS), 2020)
Brain (brain) is the center of the nervous system that regulates and mengkoordiner sabagian besat movement, behavior and function of the body, blood pressure, body fluid balance and body temperature. Brain tumors (brain) is the occurrence of abnormal cells in the brain continuously so that interfere with the function of the brain (brain). To show abnormalities in the brain (brain) tumors caused by radiological examination with CT Scan Brain (brain). CT Scan tool used Brand Toshiba, Asterion 4 / helical (spiral). The results of examination with diagnosis as Brain Tumors (brain).